Molecular characterization of Aeromonas hydrophila and development of recombinant cells vaccine expressing outer membrane proteins against its in african catfish (Clarias gariepinus Burchell) - Matusin, Saleema (2015)
Aeromonas hydrophila act as primary pathogen causing high mortality rate especially in freshwater fish, resulting big losses to farmers. Vaccination is one of the approaches to prevent bacterial infection in fish. At present, there is no commercial vaccine for protecting farmed fish against A. hydrophila, although studies have proved that vaccination may provide protection. The studies were conducted to develop a recombinant cells vaccine expressing the immunogenic genes of OmpTs and OmpW of A. hydrophila strain Ah1sa5 and to determine the protective efficacy of the developed vaccine. Five strains of Aeromonas sp.isolated from diseased freshwater fish were identified as A. hydrophila by phenotypic identification, characterized by 16S rRNA and Internal Transcribed Spacer Region (ITS) genes sequencing. The nBLAST analysis showed high percentage of similarity with other A. hydrophila strains published in Genbank obtained between 95 % - 98 %. A single strain, Ah1sa5 was selected, and used for the construction of recombinant cells vaccine by identifying the immunogenic genes of interest, the outer membrane protein (OMP) OmpTs and OmpW. The genes were amplified by PCR using specific primers and cloned into pET102/D-TOPO® vector. The OmpTs and OmpW genes showed approximately 1000 bp and 600 bp of open reading frame (ORF) and encoded a protein of 265 and 204 amino acid residues respectively. Expression of the target proteins done by SDS-PAGE and Western immunoblotting analysis revealed the expressed fusion proteins of pET102/D-OmpTs and pET102/DOmpW were approximately 60 kDa and 45 kDa. In-vivo study was conducted to investigate the efficacy of the developed vaccine in African catfish (Clarias gariepinus). The fishes were divided into five groups: control, placebo, and three vaccinated groups with inactivated recombinant cell vaccines which were recombinant cells OmpTs, OmpW and bivalent OmpTs+OmpW. The experiment was conducted for five weeks where fishes were vaccinated intraperitoneally at week 0 and booster at week 2. All fishes were challenged with A. hydrophila at week 4 and observation was done until week 5. The RPS was significantly higher (P<0.05) for all vaccinated groups (100 %) compared to placebo vaccine group (29.42 %). In conclusion, the inactivated recombinant cell vaccines expressing the OmpTs and OmpW protect African catfish (C.gariepinus) against A. hydrophila.